The Satisfaction Differentiation Between Conventional Counselling and Online Based Aplication Counselling Towards Adolescents - Ayu, Juwita Desri (Universitas Aisyah Pringsewu, 2022)
Media application is the most important part of a promotion for interacting. Moreover, counselling service is not only done Conventionally but also can be done by using an online application. The purposes of this research are to know the satisfaction differentiation level and comparison of the average satisfaction level between Conventional counselling and Online based application counselling. This research is Quantitative research. This research used a Cluster sample. The research population is 340 adolescents, and the sample of this research is 184 adolescents. The research design used Quasy Experimental Design by using the One Group Pretest-Posttest Design Approach. The data analysis used Non-Parametric by using Wilcoxon-Test. The frequency distribution level of satisfaction Conventional counselling is found 126 persons (68,48%) unsatisfied and 58 persons (31,52%) satisfied. The frequency distribution level of satisfaction Online counselling is found 53 persons (28,80%) unsatisfied and 131 persons (71,20%) satisfied. The result of statistic test is found P-value = 0.000 (less than 0.05). It showed that there is a differentiation of satisfaction between Conventional counselling and Online based application counselling towards adolescents in Junior High School 1 the Gadingrejo year of 2018. The average satisfaction level of Conventional counselling is 4.1777. The average satisfaction level of Online based application counselling is 4.5587, it means that the average satisfaction level of Online based application counselling is higher than the average satisfaction level of Conventional counselling. It can be suggested that Online based application counselling can be used as an innovation in giving adolescent reproductive health counselling. Abstrack: Aplikasi media merupakan bagian terpenting dalam sebuah promosi untuk berinteraksi. Sehinggapelayanan konseling tidak hanya dilakukan secara Konvensional, tetapi dapat juga dilakukanmelalui Online. Tujuan dari penelitian ini adalah mengetahui perbedaan tingkat kepuasan dan perbandingan rata-rata tingkat kepuasan antara konseling Konvensional dan konseling berbasisaplikasi Online. Jenis penelitian yang digunakan adalah Kuantitatif. Penelitian ini menggunakan Cluster Sampling. Populasi dalam penelitian yaitu 340 remaja dan sampel penelitian ini adalah 184 remaja. Rancangan penelitian yang digunakan adalah Quasi Experimental Design dengan pendekatan One Group Pretest-Posttest Design. Analisa data yang digunakan adalah analisa Non-Parametrik dengan menggunakan Wilcoxon Test. Distribusi frekuensi tingkat kepuasan konseling Konvensional didapatkan 126 orang (68,48%) tidak puas dan 58 orang (31,52%) puas. Distribusi frekuensi tingkat kepuasan konseling berbasis aplikasi Online didapatkan 53 orang (28,80%) yang tidak puas dan 131 orang (71,20%) yang puas terhadap konseling berbasis aplikasi Online. Hasil uji statistik didapatkan P-value = 0.000(kurang dari 0,05). Hal tersebut menunjukkan bahwa terdapat perbedaan tingkat kepuasan antara konseling Konvensional dan konseling berbasis aplikasi Online. Pada konseling Konvensional didapatkan mean = 4.1777. Pada tingkat kepuasan konseling berbasis aplikasi Online didapatkan mean =4.5587, yang artinya rata-rata tingkat kepuasan konseling berbasis aplikasi Online lebih tinggi dibandingkan denganrata-rata tingkat kepuasan konseling Konvensional. Saran dari penelitianini adalah dapat dimanfaatkannya konseling berbasis aplikasi Online sebagai salah satu bentuk inovasi dalam pemberian pelayanan konseling kesehatan reproduksi remaja.